2014
DOI: 10.1016/j.antiviral.2014.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the papain-like protease of MERS coronavirus reveals unusual, potentially druggable active-site features

Abstract: The Middle-East Respiratory Syndrome coronavirus (MERS-CoV) causes severe acute pneumonia and renal failure. The MERS-CoV papain-like protease (PL(pro)) is a potential target for the development of antiviral drugs. To facilitate these efforts, we determined the three-dimensional structure of the enzyme by X-ray crystallography. The molecule consists of a ubiquitin-like domain and a catalytic core domain. The catalytic domain displays an extended right-hand fold with a zinc ribbon and embraces a solvent-exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
122
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(128 citation statements)
references
References 55 publications
5
122
1
Order By: Relevance
“…Our structure contains the second loop (BL2) that was not defined in another recently solved apo structure of MERS-PLpro (PDB ID: 4P16). 25 That structure and our structure are almost identical except for our structure defining the BL2 loop and two different cysteine modifications. This BL2 loop plays a crucial role in SARS-PLpro inhibitor binding according to four currently available x-ray crystal structures in complex with four different inhibitors.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…Our structure contains the second loop (BL2) that was not defined in another recently solved apo structure of MERS-PLpro (PDB ID: 4P16). 25 That structure and our structure are almost identical except for our structure defining the BL2 loop and two different cysteine modifications. This BL2 loop plays a crucial role in SARS-PLpro inhibitor binding according to four currently available x-ray crystal structures in complex with four different inhibitors.…”
Section: Resultsmentioning
confidence: 59%
“…MERS-PLpro is composed of four distinct domains, an ubiquitin-like (Ubl)-domain, thumb, palm, and zinc fingers (Figure 2A). The overall structure of MERS-PLpro resembles that of SARS-PLpro 21, 25 with an α carbon RMSD of 1.2 Å. There are minor structural deviations of the Ubl, thumb and palm domains between MERS-PLpro and SARS-PLpro.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…In this context, the L106W mutation of the MERS CoV Plpro resulted in a drastic increase in deubiquitinating activity. 10) In addition, the mutation of SARS Plpro to residues similar to MERS CoV amino acids resulted in the profound loss of deubiquitinating activity. 10,20) Therefore, MERS CoV Plpro naturally has lower deubiquitinating activity compared with SARS CoV Plpro.…”
Section: Resultsmentioning
confidence: 99%
“…The Ubl domain is conserved in most CoVs including MERS CoV and SARS CoV, while the transmissible gastroenteritis CoV lacks the Ubl domain. 10,11) In studies related to the SARS CoV, Ubl was found to interfere with the IRF3 and nuclear factor-kappaB (NF-κB) antiviral pathways.…”
mentioning
confidence: 99%